2019
DOI: 10.5455/medarh.2019.73.28-31
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty of Subclavian Artery Lesions

Abstract: Introduction: Percutaneous transluminal angioplasty (PTA) is one of the treatment options for stenotic and obstructive lesions of the subclavian artery. Aim: To evaluate initial and long-term results of percutaneous transluminal angioplasty of subclavian artery lesions. Methods: During period February 2016 to December 2017, 26 patients (12 men and 14 women) with significant subclavian artery stenosis and occlusion were admitted and underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…PTA uses an inflation balloon to expand at the vascular stenosis to relieve the vascular stenosis, which can reduce the damage caused by the stent coating to the diseased blood vessel [ 6 ]. It is mainly to treat complex lesions such as tortuous, diffuse, and severe stenosis, but the interaction between the balloon and the blood vessel can easily cause damage to the blood vessel wall [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTA uses an inflation balloon to expand at the vascular stenosis to relieve the vascular stenosis, which can reduce the damage caused by the stent coating to the diseased blood vessel [ 6 ]. It is mainly to treat complex lesions such as tortuous, diffuse, and severe stenosis, but the interaction between the balloon and the blood vessel can easily cause damage to the blood vessel wall [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTA is a minimally invasive procedure that has been shown to be effective in improving symptoms and restoring blood flow in patients with subclavian artery stenosis [ 3 , 11 ]. There remains some debate regarding the optimal treatment approach for subclavian artery stenosis, particularly in terms of the use of medical management versus interventional procedures [ 6 , 12 ]. However, a recent cohort study of 100 patients demonstrated that medical management when combined with either PTA or bypass surgery improved all-cause mortality by over three-fold and lowered adverse cardiovascular outcomes, compared to medical management alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subclavian artery stenosis has been shown to affect about 9% of patients with known PAD. 2 Also, half of patients with subclavian artery disease might have coronary artery disease, 3 and renal artery stenosis often is associated. 4 The symptoms caused by each stenotic segment are well known, but prioritizing the investigations and interventional treatment for each atherosclerotic involvement can be a challenge, especially if they are diagnosed in the same patient simultaneously.…”
Section: Introductionmentioning
confidence: 99%